2015
DOI: 10.4103/0973-1482.138008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of effect of transcutaneous electrical nerve stimulation on salivary flow rate in radiation induced xerostomia patients: A pilot study

Abstract: The present study gave us an insight about the effectiveness of TENS therapy in stimulating salivary flow in healthy subjects and it is very effective when used in conjunction with radiation therapy by reducing the side-effects of radiation therapy. Hence, TENS therapy can be used as an adjunctive method for the treatment of xerostomia along with other treatment modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 5 publications
1
31
1
Order By: Relevance
“…The present findings show that the median of the stimulated salivary flow increased by 100% in patients with RT-induced hyposalivation. In the study conducted by Lakshman et al (12) , TENS (500Hz) was used in bilateral parotid glands. The authors found an increase in salivary flow with a variation of 3.7% to 140% in the intervention groups.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The present findings show that the median of the stimulated salivary flow increased by 100% in patients with RT-induced hyposalivation. In the study conducted by Lakshman et al (12) , TENS (500Hz) was used in bilateral parotid glands. The authors found an increase in salivary flow with a variation of 3.7% to 140% in the intervention groups.…”
Section: Discussionmentioning
confidence: 99%
“…Another point to consider is the long-term effect of TENS. Some studies (12,26) tried to find out if the increase of saliva would continue over time; however, they are uncontrolled trials and/or have reduced samples. Thus, despite their results, they do not have enough theoretical bases to justify the choice of this method for treatment of hyposalivation after RT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations